2020
DOI: 10.1364/oe.401933
|View full text |Cite
|
Sign up to set email alerts
|

Practical sensorless aberration estimation for 3D microscopy with deep learning

Abstract: Estimation of optical aberrations from volumetric intensity images is a key step in sensorless adaptive optics for 3D microscopy. Recent approaches based on deep learning promise accurate results at fast processing speeds. However, collecting ground truth microscopy data for training the network is typically very difficult or even impossible thereby limiting this approach in practice. Here, we demonstrate that neural networks trained only on simulated data yield accurate predictions for real experimental image… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 31 publications
(47 reference statements)
0
33
0
Order By: Relevance
“…According to the recently published papers by Saha et al, it can be confirmed that RMSE parameter is used as a quantitative index for the analysis of the utility of deep learning techniques in 3D microscopy images [ 31 ]. In addition, according to a study conducted at Linden et al, the RMSE evaluation parameter was used to confirm the difference between true and estimation data when analyzing the usefulness of the image super resolution algorithm for microscope images [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the recently published papers by Saha et al, it can be confirmed that RMSE parameter is used as a quantitative index for the analysis of the utility of deep learning techniques in 3D microscopy images [ 31 ]. In addition, according to a study conducted at Linden et al, the RMSE evaluation parameter was used to confirm the difference between true and estimation data when analyzing the usefulness of the image super resolution algorithm for microscope images [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, important advances have also been made to improve SPT and single-molecule SR imaging in densely labeled samples using deep learning (for a review, see e.g., Möckl et al, 2020a ). These developments include using neural nets to optimize and localize engineered PSFs faster and for overlapping emitters (Nehme et al, 2018 , 2020 ; Zhang et al, 2018 ), phase retrieval of aberrations, and background correction (Paine and Fienup, 2018 ; Möckl et al, 2019b , 2020b ; Saha et al, 2020 ). The next steps in this field are to standardize controls to ensure the validity of the analysis, as well as to make these approaches more easily accessible and comparable for a wide range of users.…”
Section: Discussionmentioning
confidence: 99%
“…Wavefront-sensorless AO methods are commonly used because they require no extra hardware for direct wavefront sensing and, hence, allow for simpler optical designs and avoid non-common-path sensing errors. A range of wavefront-sensorless AO schemes exist, such as modal [ 9 ], pupil segmentation zonal [ 10 ], deep learning [ 11 ], and blind searching algorithm methods [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. When based on the modal method, the correction speed of the system is fast, but the performance of the control method depends on an accurate mathematical model, and the range of correcting aberrations is limited.…”
Section: Introductionmentioning
confidence: 99%